Science and Sustainability in Food - Vaz, A.; Trindade, A.P.; Pedro, P.; Henriques, C.; Sequeira, L.; Zaragoza, M.; Viegas, M. (Open Schools Journal for Open Science, 2020)
In this project we studied the aquaponics system that allows the simultaneous production of some species of vegetables and fish. In this way, it allows the identification of the circular economy system, present in this production circuit. When feeding fish in an aquarium, the excrement produced by them is rich in nutrients that feed the plants that, in turn, filter the water for the fish. With a water pump, that keeps the water in circulation, a continuous closed circuit is achieved. We concluded that, with water and energy savings, without using phytopharmaceuticals, and with naturally occurring processes, an economy of means and the food quality is guaranteed: plants and fish. In studying this, we looked for ways to obtain the material, we do the installation and maintenance of the system, performed daily tasks and monitor the growth of plants and animals, managing to use aromatic herbs for the school bar and also divulge it.